Tradisi Lisan Minangkabau sebagai Representasi Aturan Adat, Nilai Budaya, dan Fungsi Sosial - Nidya Fitri (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Minangkabau oral tradition represents an important form of intangible cultural heritage that functions as a medium for transmitting customary rules, cultural values, and social norms across generations. Through traditional proverbs (pepatah-petitih), the Minangkabau community preserves behavioral guidelines that regulate social relationships and communal life. Although previous studies have examined Minangkabau oral traditions from the perspectives of folklore, literature, and local wisdom, limited attention has been given to the interrelationship between customary rules, cultural values, and social functions. This study aims to analyze the representation of customary rules, cultural values, and social functions embedded in Minangkabau proverbs. A qualitative approach with qualitative content analysis was employed. The data comprised 20 Minangkabau proverbs collected through documentary research from customary literature, scholarly publications, and cultural documents. The analysis involved identifying oral traditions, interpreting the customary rules represented, classifying the underlying cultural values, and examining their social functions. The findings indicate that the proverbs represent ten categories of customary rules, namely religiosity, deliberation, mutual cooperation, respect, propriety, prudence, justice, leadership, solidarity, and reconciliation. These values function as mechanisms of social control, character education, conflict resolution, cultural identity preservation, and the maintenance of social harmony.